Komodifikasi Prostitusi Online sebagai Kritik atas Globalisasi - Indah Sari Rahmaini; A Zahid A Zahid (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2020)
Economic transactions titled sexuality has long been a commodity traded by the public since the colonial period. Prostitution is a classic problem that remains unresolved in Indonesia. Present prostitution becomes a paradox in the modern life of connoisseurs of globalization, so what is happening now is the commodification of prostitution which is called online prostitution. This paper focuses on describing the commodification of online prostitution as a critique of globalization that utilizes platforms / applications / websites to attract customers who are certainly different from conventional prostitution by borrowing the concept of commodification from Karl Marx. This research uses a qualitative method with descriptive type. The results of the research describe that the presence of globalization constructs the commodification of prostitution by the mechanism of using online media as a means to launch such activities. Globalization in a critical perspective must be seen as one of the threats that can attack cultural communities in the midst of the battle of digitalization in Indonesia. In wading through this problem, we certainly still must oversee all policies and good cooperation with various parties to be able to minimize the strong development of globalization, starting from strengthening legal standing, using social media wisely, to monitoring from various parties to be able to oversee all the bad possibilities that will occur through the vehicle of globalization.